The Inclusion of People with Disabilities in a Multi-Sport School: Effect of Attitudes on Children, Youth, Parents, and Instructors Towards Disability - Víquez Ulate, Fabian; Quirós Carrión, Sugey; Rodríguez-Méndez, Diego; Solano Mora, Luis (MHSalud: Revista en Ciencias del Movimiento Humano y Salud, 2020)
This study aimed to observe children, youth, parents, and instructors’ attitudes towards disability. The study intended to measure the effects of a multidisciplinary program of the Escuela Deportiva Pedagógica -EDP- (Pedagogical Sports School) of the School of Human Movement and Quality of Life, at the National University of Costa Rica. Methodology: thirty-three participants were incorporated into the study. Then, they were separated into three groups: four instructors, eleven parents, and eighteen children. The intervention consisted of participation in multisport sessions, at least two hours per week in three sport disciplines that varied from week to week over six weeks. All of them were given a questionnaire titled “Actitudes hacia las personas con discapacidad” (Attitudes towards people with disabilities). The questionnaire was applied both at the beginning and at the end of the intervention. A two-factor mixed ANOVA of 3 (groups) x 2 (measurements) with an alpha of 0.05 was used. Results: A significant interaction was found after the treatment in the dimension of “Valoración de las capacidades y limitaciones” -VCL- (Assessment of skills and limitations), F(2, 30) = 10.28, p< 0.001. There were also significant differences between measurements in the dimension of “Clasificación genérica” -CG- (generic classification), F(1, 30) = 4.884, p = 0.035, while in the dimensions of “Reconocimiento o negación de derechos” -RND- (recognition or denial of rights) and the “Implicación personal” -IP- (personal involvement) no significant differences were found (all p > 0.05). Conclusion: The results showed that the multidisciplinary programs of an inclusive nature positively modify attitudes (VCL and CG) towards the population with disabilities, but it is likely that some aspects related to attitude take longer to be changed (RND and IP).